Analisis Beban Kerja Mental Operator pada Bagian Pengantongan Semen dengan Metode National Aeronautics And Space Administration Task Load Index (NASA-TLX) - Aprilia, Nurul Suci; Nugraha; Rejeki, Yanti Sri (UNISBA Press, 2023)
Abstract. Production activities certainly can’t be separated from various resources. One of the resources that plays an important role is workers. In order to work optimally, workers need attention. One of the concerns that companies can give is to pay attention to the workload. Based on interviews with 10 workers in the packing section, including 6 workers in three rotary inline packer machines, 2 workers in chute, and 2 workers in loading channels. Some of the symptoms experienced by workers such as feeling lethargic, often sleepy, dizzy, not concentrating, losing passion to work, experiencing fever, dizziness and heart rate. Based on the symptoms of fatigue experienced by workers, it can be indicated that operators experience some complaints that are felt mentally, so there is a formulation of the problem in this study, namely